Liver rupture in a 28‐year‐old primigravida with superimposed pre‐eclampsia and hemolysis, elevated liver enzyme levels, and low platelet count syndrome. Issue 5 (10th March 2019) - Kaltofen, Till; Grabmeier, Johanna; Weissenbacher, Tobias; Hallfeldt, Klaus; Mahner, Sven; Hutter, Stefan
Abstract: Serious hepatic complications, although rare, are one of the leading causes of maternofetal morbidity and mortality in hypertensive pregnancy disorders. A 28‐year‐old primigravida was transferred to our hospital complaining of refractory epigastric pain in the 29th week of pregnancy and was subsequently admitted due to superimposed pre‐eclampsia and hemolysis, elevated liver enzyme levels, and low platelet count syndrome. Following a pathological cardiotocogram, a cesarean section was performed. The intra‐abdominal situs presented with 1000 mL of blood and a bleeding rupture of the left lobe of the liver. The trauma to the liver was surgically repaired with a suture and the patient's state was stabilized. Following the surgical procedures and neonatal intensive care, mother and newborn both recovered without residues. In order to avoid unnecessary maternal morbidity, we therefore recommend an abdominal ultrasound, beyond an obstetric focus, as an additional and sensible means of diagnostic imaging in cases of hemolysis, elevated liver enzyme levels, and low platelet count syndrome.